Refinancing risk, earnings management, and stock return - Wang, Shu Feng; Kim, Yura; Kim, Seonmi; Song, Kyojik “Roy” (Research in International Business and Finance, 2024)
This paper presents empirical evidence that a firm's refinancing risk affects its income-increasing earnings management. We find that refinancing risk is positively associated with discretionary accruals and that interaction between leverage and refinancing risk aggravates the incentive to manage earnings. We also find that the firm's cash holdings attenuate the adverse effect of the refinancing risk on the earnings management. In addition, we document that the discretionary accruals of firms with high refinancing risk are negatively associated with one-year-ahead stock returns. Our results suggest that firms with higher refinancing risk have opportunistic incentives to inflate earnings to appear financially healthy, but the effect of earnings management is temporary.
Keywords: Cash holdings; Discretionary accruals; Earnings management; Refinancing risk; Stock return